Current Understanding of Nasal Epithelial Cell Mis-Differentiation - Scherzad A; Hagen R; Hackenberg S (Dove Medical Press, 2019)
Agmal Scherzad, Rudolf Hagen, Stephan Hackenberg Department of Otorhinolaryngology, Plastic, Aesthetic and Reconstructive Head and Neck Surgery, Julius Maximilian University of Wuerzburg, Würzburg 97080, GermanyCorrespondence: Agmal ScherzadDepartment of Otorhinolaryngology, Plastic, Aesthetic and Reconstructive Head and Neck Surgery, Julius Maximilian University of Wuerzburg, Würzburg 97080, GermanyEmail Scherzad_A@ukw.deAbstract: The functional role of the respiratory epithelium is to generate a physical barrier. In addition, the epithelium supports the innate and acquired immune system through various cytokines and chemokines. However, epithelial cells are also involved in the pathogenesis of various respiratory diseases, some of which are mediated by increased permeability of the mucosal membrane or disturbed mucociliary transport. In addition, it has been shown that epithelial cells are involved in the development of inflammatory respiratory diseases. The following review article focuses on the aspects of epithelial mis-differentiation, in particular with respect to nasal mucosal barrier function, epithelial immunogenicity, nasal epithelial–mesenchymal transition and nasal microbiome.Keywords: nasal mucosal barrier function, tight junction, epithelial–mesenchymal transition, microbiome